Femtosecond laser inscription of fiber bragg gratings with low insertion loss and minor polarization dependence - Zhang, Lin; Kalli, Kyriacos; Allsop, Thomas P.; Davies, Edward M.; Webb, David J.; Koutsides, Charalambos (My University, 2010)
The inscription of low insertion loss and negligibly polarization dependent fiber Bragg gratings inscribed using a femtosecond laser system is reported. Insertion losses were <0.4dB/20mm and polarization wavelength shift of <5pm, with transmission changes <0.1dB. 2010 Optical Society of America.
Keywords: Femtosecond laser inscriptions; Femtosecond laser system; Low insertion loss; Polarization dependence; Wavelength shift; Fiber bragg gratings; Glass; Light sensitive materials; Photosensitivity; Polarization; Waveguides; Ultrashort pulses